FOULING ORGANISMS ASSOCIATED WITH MANGROVE IN AMBON INNER BAY - Yosmina Tapilatu; Daniel Pelasula (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2012)
Limited literatures exist on fouling organisms attached to mangrove in Ambon Inner Bay (AIB). The purpose of this research is to obtain updated information on fouling organism in this ecosystem. Samplings were carried out in two periods, representing first transition period and west monsoons, at two different locations in AIB (Poka and Kate-kate). Methods used were direct observation and descriptive exploration during sampling. Fouling organisms and mangrove type were identified using identification books. The results obtained indicate that predominant organisms belonged to mollusks and crustacea. Four gastropod species (Littorina scabra, Nerita oualaniens, Terebralia sulcata, Cassidula nucleus) and one bivalve (Saccostrea cucullata) were identified. Clibanarius ambonensis and Cardisoma carnifex were the species identified from crustacea group. Type of mangrove found, either naturally or through replanting program in Poka were Rhizophora apiculata, R. stylosa and Sonneratia alba. There were four different species found in Kate-kate (S. alba, R. apiculata, Ceriops tagal and Aegiceras corniculatum).Keywords: fouling organisms, mangrove ecosystem, Ambon Inner Bay